The Influence Of Internal Control And Information Technology On Financial Report Quality With Human Resource Competence - Nur Azizah; Yudi Yudi; Rita Friyani (CV. AFDIFAL MAJU BERKAH, 2025)
This study aims to examine the influence of the internal control system and the use of information technology on the quality of the Jambi Provincial Government's financial reports with human resource competency as a moderating variable. The study population was all Regional Apparatus Organizations (OPD) in Jambi Province with a sample of 84 respondents consisting of the Head of Finance Subdivision, Finance Treasurer, and Finance Staff. The research method used a quantitative approach with multiple linear regression analysis and interaction test (Moderated Regression Analysis) with the help of SPSS version 30. The results showed that the internal control system and the use of information technology had an effect on the quality of financial reports. In addition, human resource competency was proven to significantly moderate the relationship between the internal control system and the use of information technology on the quality of financial reports. This indicates that the successful implementation of the internal control system and information technology is highly dependent on the level of human resource competency in managing and operating both. This research provides important implications for the Jambi Provincial Government to continue improving internal controls, technology utilization, and human resource competency to enhance the quality of accurate, reliable, and transparent financial reports. Furthermore, it is recommended that future research include additional variables and expand the sample size to obtain more comprehensive results.